The influence of dietary simulating solvents on a recent composite topography (in vitro study ) (Mustansiria Dental Journal, 2005)
Objective: study the influence of dietary simulating liquids on the micro hardness ,surface roughness, and color stability of polished and non-polished organically modifiedceramic, at different storage time .Methods: 240 samples were prepared and then stored in a dark phial containingdistilled water (D.W) at 37C for 7 days before conditioning then the samples divided into3 groups, 80 samples in each, and stared in the conditioning liquids at 40 C for 1, 7 and41 days At the end of each conditioning time the specimens were subjected to colorcomparison test, surface roughness test (RA) and microhardness test Vickers hardnessnumber (VHN .)Results & conclusion Increase aging time will increase the VHN value anddecrease the Ra value of ormocer specially for the control group (aged in D.W). Aging in( food stimulated liquids) F SLs produced an increase in VHN value but to a degree lessthan that of D.W. which in turn produced significant effect of these liquids on Ormocerhardness with time in comparison to the control group Most effect will be seen with 50%Ethanol VHN and color stability. The effect of FSLs on Ormocer VHN were on longterm duration (ll days) while for color change ;(7 days) is the critical time and after thefirst week no additional color will take place. Surface roughness of polished and non -polished Ormocer was not affected by any FSLs and at any aging time. Polishing ofOrmocer will increase the VHN value and Ra value for all FSLs and for all timeintervals .Change in organic base matrix of composite resins is of great value for improvingcmposite properties and durability .